Slurry, polishing method, and manufacturing method for semiconductor parts

A cerium oxide-based slurry with tailored Hansen solubility parameters enhances silicon oxide polishing rates, addressing inefficiencies in CMP processes for semiconductor manufacturing.

JP7601106B2Active Publication Date: 2024-12-17RESONAC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022553800
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-09-15
Publication Date
2024-12-17
Estimated Expiration
2041-09-15

AI Technical Summary

Technical Problem

Existing CMP polishing liquids containing cerium oxide abrasive grains are inefficient in removing silicon oxide, requiring improved polishing rates for semiconductor manufacturing processes.

Method used

A slurry comprising cerium oxide abrasive grains with specific Hansen solubility parameters and composition is developed, enhancing the polishing rate of silicon oxide through improved dehydration condensation reactions.

Benefits of technology

The slurry achieves a polishing rate of silicon oxide exceeding 4600 Å/min, effectively addressing the inefficiencies of conventional CMP polishing liquids.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601106000001
    Figure 0007601106000001
Patent Text Reader

Abstract

The present invention is a slurry containing abrasive grains, a compound X, and water, wherein the abrasive grains contain a cerium oxide, and the hydrogen bonding parameter dH of the Hansen solubility parameters of the compound X is 15.0 MPa1 / 2 or more. The present invention provides a polishing method for polishing a surface to be polished by using said slurry.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to slurries, polishing methods, methods of manufacturing semiconductor components, and the like. [Background technology]

[0002] In recent years, the importance of processing techniques for higher density and finer processing has been increasing in the manufacturing process of semiconductor elements. One of the processing techniques, CMP (Chemical Mechanical Polishing), is an essential technique for forming shallow trench isolation (STI), planarizing premetal insulating materials or interlayer insulating materials, forming plugs or buried metal wiring, etc., in the manufacturing process of semiconductor elements. As a CMP polishing solution, a CMP polishing solution containing abrasive grains containing cerium oxide is known (see, for example, Patent Documents 1 and 2 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-106994 [Patent Document 2] Japanese Patent Application Publication No. 08-022970 Summary of the Invention [Problem to be solved by the invention]

[0004] In some cases, it is required to polish and quickly remove a member containing silicon oxide using a CMP polishing liquid containing abrasive grains containing cerium oxide. For a slurry used as such a CMP polishing liquid, it is required to improve the polishing rate of silicon oxide.

[0005] An object of one aspect of the present disclosure is to provide a slurry capable of improving the polishing rate of silicon oxide.Another object of the present disclosure is to provide a polishing method using the slurry.Another object of the present disclosure is to provide a method for manufacturing a semiconductor component using the polishing method. [Means for solving the problem]

[0006] One aspect of the present disclosure is a method for producing a cerium oxide abrasive comprising the steps of: (a) providing a cerium oxide abrasive grain having a hydrogen bond term dH of a Hansen solubility parameter of 15.0 MPa; 1 / 2 Thus, a slurry is provided.

[0007] Another aspect of the present disclosure provides a polishing method for polishing a surface to be polished using the above-mentioned slurry.

[0008] According to such a slurry and polishing method, the polishing rate of silicon oxide can be improved.

[0009] Another aspect of the present disclosure provides a method for producing a semiconductor component, comprising: obtaining a semiconductor component by dicing a member having a polished surface polished by the above-described polishing method. Effect of the Invention

[0010] According to one aspect of the present disclosure, it is possible to provide a slurry capable of improving the polishing rate of silicon oxide. According to another aspect of the present disclosure, it is possible to provide a polishing method using the slurry. According to another aspect of the present disclosure, it is possible to provide a manufacturing method of semiconductor components using the polishing method. According to another aspect of the present disclosure, it is possible to provide application of the slurry to polishing of silicon oxide. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, embodiments of the present disclosure will be described. However, the present disclosure is not limited to the following embodiments.

[0012] In this specification, the numerical range indicated by "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. The numerical range "A or more" means a range exceeding A and A. The numerical range "A or less" means a range less than A and A. In the numerical ranges described in stages in this specification, the upper limit or lower limit of a numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of a numerical range of another stage. In the numerical ranges described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. "A or B" may include either A or B, or may include both. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. The content of each component in the composition means the total amount of the multiple substances present in the composition when multiple substances corresponding to each component are present in the composition, unless otherwise specified. The hydroxyl group does not include the OH group contained in the carboxy group. The hydrogen bond term dH, dispersion term dD, and polarization term dP of the Hansen solubility parameters described below are in units of MPa. 1 / 2 In the following, the unit is MPa. 1 / 2 The display will be omitted as appropriate.

[0013] The slurry according to this embodiment contains abrasive grains, a compound X, and water. The abrasive grains contain cerium oxide, and the hydrogen bond term dH of the Hansen solubility parameter of the compound X is 15.0 MPa. 1 / 2 The slurry according to this embodiment can be used as a polishing slurry (for example, a CMP polishing liquid).

[0014] According to the slurry of this embodiment, it is possible to improve the polishing rate of silicon oxide, and a polishing rate of silicon oxide of 4600 Å / min or more can be obtained. Furthermore, according to the slurry of this embodiment, it is possible to improve the polishing rate of silicon oxide derived from TEOS (tetraethoxysilane) (silicon oxide obtained using TEOS, for example, silicon oxide of a TEOS film). The reason why the polishing rate of silicon oxide is improved is not necessarily clear, but the present inventor presumes it to be as follows. That is, since the hydrogen bond term dH of the Hansen solubility parameter of compound X is large, compound X is likely to act on the abrasive grains containing cerium oxide and silicon oxide (for example, silicon oxide derived from TEOS) via hydrogen bonds. Therefore, the dehydration condensation reaction between the abrasive grains and silicon oxide is likely to proceed, and the polishing rate of silicon oxide is improved. However, the cause is not limited to the above content. According to this embodiment, it is possible to provide a polishing rate adjustment method for adjusting the polishing rate of silicon oxide based on the hydrogen bond term dH of the Hansen solubility parameter.

[0015] The slurry according to the present embodiment contains abrasive grains containing cerium oxide. In this specification, the term "abrasive grains" refers to a collection of a plurality of particles, but for convenience, a single particle constituting the abrasive grains may be referred to as an abrasive grain. The abrasive grains may contain one or more types of particles. Examples of materials constituting the abrasive grains other than cerium oxide include inorganic substances such as silica, alumina, zirconia, titania, germania, and silicon carbide; and organic substances such as polystyrene, polyacrylic acid, and polyvinyl chloride.

[0016] From the viewpoint of easily improving the polishing rate of silicon oxide, the content of cerium oxide in the abrasive grains may be more than 95 mass%, 98 mass% or more, 99 mass% or more, 99.5 mass% or more, or 99.9 mass% or more based on the entire abrasive grains (the entire abrasive grains contained in the slurry, or the entire particles constituting the abrasive grains). The abrasive grains may be substantially composed of cerium oxide (substantially 100 mass% of the abrasive grains is cerium oxide).

[0017] The abrasive grains may be colloidal, and may include, for example, colloidal ceria. A slurry containing colloidal abrasive grains is a suspension of abrasive grains, and the cerium oxide forming the abrasive grains is dispersed in water. The colloidal abrasive grains can be obtained, for example, by a liquid phase method, and are abrasive grains derived from the liquid phase method. Examples of the liquid phase method include a colloid method, a hydrothermal synthesis method, a sol-gel method, a neutralization decomposition method, a hydrolysis method, a chemical precipitation method, a co-precipitation method, an atomizing method, a reverse micelle method, and an emulsion method. The abrasive grains may have grain boundaries or may not have grain boundaries.

[0018] As the colloidal abrasive, abrasive particles having a positron lifetime of τ2 of 0.3650 ns or less among the positron lifetimes τ1 to τ4 can be used. 22 It is the time it takes for a positron emitted from Na to annihilate with an electron, and can be used as a probe for lattice defects on the sub-nanometer to nanometer order, free volume, and other ultrafine voids. In other words, the shorter the positron lifetime, the denser the particle.

[0019] The positron lifetime can be measured using PAS Type L-II manufactured by Toyo Seiko Co., Ltd. The abrasive grains are vacuum dried at room temperature (25°C) for 24 hours to obtain a powder, which is then placed in a powder measurement box and set in the positron source unit. Measurements are performed until the accumulated number of counts reaches 1 million. The lifetime histogram is separated into two components and analyzed using IPALM, the software provided with the device. 22 Some of the positrons emitted from Na are annihilated by the positron source itself, such as Kapton and adhesive, and these components are mixed into the measurement results, so the analysis assumes that the proportion of Kapton is 30%. Of the obtained positron lifetimes τ1 to τ4, τ1 and τ2 correspond to the positron lifetime originating from the sample, τ3 corresponds to the positron lifetime originating from Kapton, and τ4 corresponds to the positron lifetime originating from the adhesive. In addition, τ1 corresponds to a small void such as a single vacancy, and τ2 corresponds to a void in which multiple voids are clustered.

[0020] As the colloidal abrasive grains, abrasive grains that show regular diffraction spots in electron beam diffraction of a transmission electron microscope (TEM) can be used. For example, when colloidal ceria is used as the abrasive grains, when two adjacent diffraction spots A1 and A2 and a diffraction spot B adjacent to the diffraction spots A1 and A2 are observed in the diffraction spots obtained when an electron beam is applied perpendicularly to the ceria (111) plane, the distance R between the diffraction spots (the distance between the diffraction spots A1 and B, and the distance between the diffraction spots A2 and B) is 1.6 to 2.2 Å, and the minimum value of the angle α formed by the diffraction spots A1 and A2 with respect to the diffraction spot B is 58 to 62° may account for 50% or more of the abrasive grains.

[0021] A JEM-2100F manufactured by JEOL Ltd. can be used to observe the abrasive grains and measure the distance R and angle α between the diffraction spots. Electron beam diffraction can be performed on each abrasive grain of a TEM grit with the abrasive grains attached thereto under conditions of an acceleration voltage of 200 kV, an electron beam wavelength of 2.508 pm, and a camera length of 30 cm, and the distance R and angle α can be measured. The distance R and angle α can be measured at least three points for each abrasive grain, and the average value can be used. The measurement is performed on all abrasive grains that are confirmed to be 100 or more in one field of view in TEM observation under any magnification, and the percentage of abrasive grains that satisfy the above conditions can be calculated.

[0022] The average particle size of the abrasive grains may be in the following range: The average particle size of the abrasive grains can be adjusted by natural settling, pulverization, dispersion, filtration, etc. For example, the particle size adjustment may be performed after mixing the constituent components of the slurry.

[0023] The average particle diameter D50 of the abrasive grains may be 1 nm or more, 3 nm or more, 5 nm or more, 10 nm or more, 30 nm or more, 50 nm or more, 80 nm or more, 100 nm or more, more than 100 nm, 120 nm or more, 130 nm or more, or 140 nm or more, from the viewpoint of easily improving the polishing rate of silicon oxide. The average particle diameter D50 of the abrasive grains may be 500 nm or less, 300 nm or less, 200 nm or less, 180 nm or less, 160 nm or less, 155 nm or less, 152 nm or less, 150 nm or less, or 147 nm or less, from the viewpoint of easily improving the polishing rate of silicon oxide. From these viewpoints, the average particle diameter D50 of the abrasive grains may be 1 to 500 nm. The average particle diameter D50 of the abrasive grains may be 142 nm or more, 143 nm or more, 144 nm or more, 145 nm or more, or 147 nm or more. The average particle size D50 of the abrasive grains may be 145 nm or less, 144 nm or less, 143 nm or less, 142 nm or less, or 140 nm or less. The average particle size D50 of the abrasive grains means the 50% particle size of the cumulative distribution on a volume basis, and can be measured, for example, by a laser diffraction particle size distribution analyzer.

[0024] The volume average particle diameter MV of the abrasive grains may be 1 nm or more, 3 nm or more, 5 nm or more, 10 nm or more, 30 nm or more, 50 nm or more, 80 nm or more, 100 nm or more, more than 100 nm, 120 nm or more, 130 nm or more, 140 nm or more, 145 nm or more, or 147 nm or more, from the viewpoint of easily improving the polishing rate of silicon oxide. The volume average particle diameter MV of the abrasive grains may be 500 nm or less, 300 nm or less, 200 nm or less, 180 nm or less, 160 nm or less, 155 nm or less, or 152 nm or less, from the viewpoint of easily improving the polishing rate of silicon oxide. From these viewpoints, the volume average particle diameter MV of the abrasive grains may be 1 to 500 nm. The volume average particle diameter MV of the abrasive grains may be 150 nm or more, or 152 nm or more. The volume average particle diameter MV of the abrasive grains may be 150 nm or less, or 147 nm or less. The volume average particle size MV of the abrasive grains can be measured, for example, by a laser diffraction particle size distribution analyzer.

[0025] The content of the abrasive grains may be in the following range based on the total mass of the slurry from the viewpoint of easily improving the polishing rate of silicon oxide. The content of the abrasive grains may be 0.01 mass% or more, 0.03 mass% or more, 0.05 mass% or more, 0.08 mass% or more, 0.10 mass% or more, 0.20 mass% or more, or 0.25 mass% or more. The content of the abrasive grains may be 10 mass% or less, 5.0 mass% or less, 3.0 mass% or less, 1.0 mass% or less, less than 1.0 mass%, 0.80 mass% or less, 0.50 mass% or less, less than 0.50 mass%, 0.40 mass% or less, 0.30 mass% or less, or 0.25 mass% or less. From these viewpoints, the content of the abrasive grains may be 0.01 to 10 mass%.

[0026] In order to improve the polishing rate of silicon oxide, the slurry according to this embodiment has a hydrogen bond term dH (unit: MPa 1 / 2 ) is 15.0 or more.

[0027] From the viewpoint of easily improving the polishing rate of silicon oxide, the number of carbon atoms in compound X may be 3 or more, or 4 or more. From the viewpoint of easily improving the polishing rate of silicon oxide, the number of carbon atoms in compound X may be 100 or less, 80 or less, 60 or less, 50 or less, 45 or less, 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 10 or less, 8 or less, 7 or less, 6 or less, 5 or less, or 4 or less. From these viewpoints, the number of carbon atoms in compound X may be 3 to 100. The number of carbon atoms in compound X may be 5 or more, or 6 or more. The number of carbon atoms in compound X may be 3 or less.

[0028] Hansen solubility parameters (HSP) are the three energy terms (unit: MPa) that make up the dispersion state of a substance. 1 / 2The Hansen solubility parameters of a compound can be calculated based on the structure of the compound using, for example, the Hansen Solubility Parameters in Practice (HSPiP) program (ver. 5.3.02).

[0029] The hydrogen bond term dH may be in the following ranges from the viewpoint of adjusting the polishing rate of silicon oxide. The hydrogen bond term dH may be 15.5 or more, 16.0 or more, 16.5 or more, 17.0 or more, 17.5 or more, 18.0 or more, 18.5 or more, 19.0 or more, 19.1 or more, 19.3 or more, or 19.4 or more. The hydrogen bond term dH may be 50.0 or less, 40.0 or less, 30.0 or less, 25.0 or less, 24.0 or less, 23.8 or less, 23.7 or less, 23.5 or less, 23.0 or less, 22.5 or less, 22.0 or less, 21.5 or less, 21.0 or less, 20.5 or less, 20.0 or less, or 19.5 or less. From these viewpoints, the hydrogen bond term dH may be 15.0 to 50.0. The hydrogen bond term dH may be 19.5 or more, 20.0 or more, 20.5 or more, 21.0 or more, 21.5 or more, 22.0 or more, 22.5 or more, 23.0 or more, 23.5 or more, 23.7 or more, 23.8 or more, or 24.0 or more. The hydrogen bond term dH may be 19.4 or less, 19.3 or less, 19.1 or less, 19.0 or less, or 18.5 or less. The hydrogen bond term dH tends to increase, for example, as the number of functional groups (hydroxyl groups, carboxyl groups, etc.) that form hydrogen bonds in compound X increases.

[0030] From the viewpoint of easily improving the polishing rate of silicon oxide, the dispersion term dD of compound X may be 22.0 or less, 21.5 or less, 21.0 or less, 20.5 or less, 20.0 or less, 19.5 or less, 19.0 or less, 18.5 or less, 18.0 or less, less than 18.0, 17.9 or less, 17.8 or less, 17.7 or less, 17.6 or less, 17.5 or less, 17.3 or less, 17.2 or less, 17.0 or less, less than 17.0, or 16.9 or less. From the viewpoint of easily improving the polishing rate of silicon oxide, the dispersion term dD of the compound X may be 10.0 or more, more than 10.0, 12.0 or more, more than 12.0, 14.0 or more, more than 14.0, 15.0 or more, more than 15.0, 15.5 or more, 16.0 or more, more than 16.0, 16.1 or more, 16.3 or more, 16.5 or more, or 16.8 or more. From these viewpoints, the dispersion term dD of the compound X may be 10.0 to 22.0. The dispersion term dD of the compound X may be 16.9 or more, 17.0 or more, more than 17.0, 17.2 or more, 17.3 or more, 17.5 or more, 17.6 or more, 17.7 or more, 17.8 or more, 17.9 or more, 18.0 or more, more than 18.0, 18.5 or more, 19.0 or more, 19.5 or more, 20.0 or more, or 20.5 or more. The dispersion term dD tends to decrease as the number of polar groups (hydroxyl groups, carboxyl groups, etc.) in the compound X increases, for example.

[0031] The polarization term dP may be in the following ranges from the viewpoint of adjusting the polishing rate of silicon oxide. The polarization term dP may be 0.1 or more, 0.5 or more, 1.0 or more, 3.0 or more, 5.0 or more, 7.0 or more, 9.0 or more, 9.2 or more, 9.4 or more, 9.5 or more, 9.7 or more, 10.0 or more, 10.1 or more, 10.2 or more, 10.3 or more, 10.5 or more, 11.0 or more, 12.0 or more, 15.0 or more, or 20.0 or more. The polarization term dP may be 30.0 or less, 20.0 or less, 15.0 or less, 12.0 or less, 11.0 or less, 10.5 or less, 10.3 or less, 10.2 or less, 10.1 or less, 10.0 or less, 9.7 or less, 9.5 or less, or 9.4 or less. From these viewpoints, the polarization term dP may be from 0.1 to 30.0.

[0032] The molecular weight of the compound X may be in the following ranges from the viewpoint of adjusting the polishing rate of silicon oxide. The molecular weight of the compound X may be 50 or more, 80 or more, 100 or more, 105 or more, 110 or more, 120 or more, 121 or more, 125 or more, 130 or more, 140 or more, 150 or more, 200 or more, 300 or more, 500 or more, 700 or more, 800 or more, 1000 or more, or 1100 or more. The molecular weight of the compound X may be 3000 or less, 2000 or less, 1500 or less, 1200 or less, 1100 or less, 1000 or less, 800 or less, 700 or less, 500 or less, 300 or less, 200 or less, 150 or less, 140 or less, 130 or less, 125 or less, 121 or less, 120 or less, 110 or less, or 105 or less. From these viewpoints, the molecular weight of compound X may be 50-3,000.

[0033] From the viewpoint of easily improving the polishing rate of silicon oxide, compound X may have at least one selected from the group consisting of a hydroxy group, a carboxy group, a carboxylate group, an amino group, a thiol group, and a ureido group. Compound X does not have to have at least one selected from the group consisting of a hydroxy group, a carboxy group, a carboxylate group, an amino group, a thiol group, and a ureido group.

[0034] When compound X has a hydroxy group, the number of hydroxy groups in compound X is 1 or more, and from the viewpoint of easily improving the polishing rate for silicon oxide, may be 30 or less, 25 or less, 20 or less, 15 or less, 12 or less, 10 or less, 8 or less, 5 or less, 3 or less, or 2 or less. From these viewpoints, the number of hydroxy groups may be 1 to 30. The number of hydroxy groups may be 2 or more, or 3 or more.

[0035] When compound X has at least one selected from the group consisting of a carboxy group and a carboxylate group, the total of the carboxy group and the carboxylate group in compound X may be in the following range. From the viewpoint of easily improving the polishing rate for silicon oxide, the total of the carboxy group and the carboxylate group may be 1 or more. From the viewpoint of easily improving the polishing rate for silicon oxide, the total of the carboxy group and the carboxylate group may be 5 or less, 4 or less, 3 or less, or 2 or less. From these viewpoints, the total of the carboxy group and the carboxylate group may be 1 to 5.

[0036] From the viewpoint of easily improving the polishing rate of silicon oxide, compound X may have a hydroxyalkyl group or may have a hydroxymethyl group. From the viewpoint of easily improving the polishing rate of silicon oxide, the number of hydroxyalkyl groups in compound X may be 1, 2 or 3. From the viewpoint of easily improving the polishing rate of silicon oxide, compound X may have a branched carbon chain or may have a quaternary carbon atom.

[0037] Examples of the compound X include saturated carboxylic acids, ureido compounds (compounds having a ureido group, excluding compounds corresponding to saturated carboxylic acids), thiol compounds (compounds having a thiol group, excluding compounds corresponding to saturated carboxylic acids or ureido compounds), and polyols (excluding compounds corresponding to saturated carboxylic acids, ureido compounds, or thiol compounds). Examples of the saturated carboxylic acids include hydroxyisobutyric acid (e.g., 2-hydroxyisobutyric acid), 2,2-bis(hydroxymethyl)butyric acid, and 2,2-bis(hydroxymethyl)propionic acid. Examples of the ureido compounds include allantoin. Examples of the thiol compounds include cysteine ​​(e.g., L-cysteine), thioglycerol (e.g., α-thioglycerol), and the like. Examples of the polyols include trimethylolethane, and the like.

[0038] From the viewpoint of easily improving the polishing rate of silicon oxide, compound X may contain at least one selected from the group consisting of hydroxyisobutyric acid, 2,2-bis(hydroxymethyl)propionic acid, 2,2-bis(hydroxymethyl)butyric acid, allantoin, cysteine, thioglycerol, and trimethylolethane. From the viewpoint of easily improving the polishing rate of silicon oxide, compound X may be an embodiment containing hydroxyisobutyric acid, an embodiment containing 2,2-bis(hydroxymethyl)butyric acid, or an embodiment containing 2,2-bis(hydroxymethyl)propionic acid.

[0039] The content of compound X may be in the following range based on the total mass of the slurry: From the viewpoint of easily improving the polishing rate of silicon oxide, the content of compound X may be 0.0010 mass% or more, 0.0030 mass% or more, 0.0050 mass% or more, 0.0070 mass% or more, 0.010 mass% or more, 0.015 mass% or more, 0.020 mass% or more, or 0.025 mass% or more. The content of the compound X may be 10% by mass or less, 5.0% by mass or less, 1.0% by mass or less, less than 1.0% by mass, 0.70% by mass or less, 0.50% by mass or less, less than 0.50% by mass, 0.40% by mass or less, less than 0.40% by mass, 0.30% by mass or less, 0.20% by mass or less, 0.10% by mass or less, less than 0.10% by mass, 0.070% by mass or less, 0.050% by mass or less, less than 0.050% by mass, 0.030% by mass or less, or 0.025% by mass or less, from the viewpoint of easily improving the polishing rate of silicon oxide. From these viewpoints, the content of the compound X may be 0.0010 to 10% by mass. The content of compound X may be 0.030% by mass or more, 0.050% by mass or more, more than 0.050% by mass, 0.070% by mass or more, or 0.10% by mass or more, from the viewpoint of easily improving the polishing rate ratio of silicon oxide to silicon nitride.

[0040] The content of the compound X may be in the following ranges relative to 100 parts by mass of the abrasive grains. From the viewpoint of easily improving the polishing rate of silicon oxide, the content of the compound X may be 0.1 parts by mass or more, 0.5 parts by mass or more, 1 part by mass or more, more than 1 part by mass, 3 parts by mass or more, 5 parts by mass or more, 7 parts by mass or more, or 10 parts by mass or more. From the viewpoint of easily improving the polishing rate of silicon oxide, the content of the compound X may be 200 parts by mass or less, 150 parts by mass or less, 100 parts by mass or less, 70 parts by mass or less, 50 parts by mass or less, 40 parts by mass or less, less than 40 parts by mass, 30 parts by mass or less, 20 parts by mass or less, or 10 parts by mass or less. From these viewpoints, the content of the compound X may be 0.1 to 200 parts by mass. From the viewpoint of easily improving the polishing rate ratio of silicon oxide to silicon nitride, the content of the compound X may be more than 10 parts by mass, 20 parts by mass or more, 30 parts by mass or more, or 40 parts by mass or more.

[0041] The slurry according to the present embodiment contains water. The water may be contained as the remainder after removing other components from the slurry. The water content may be in the following ranges based on the total mass of the slurry. The water content may be 90.000 mass% or more, 93.000 mass% or more, 95.000 mass% or more, 97.000 mass% or more, 99.000 mass% or more, 99.200 mass% or more, 99.400 mass% or more, 99.500 mass% or more, 99.600 mass% or more, or 99.700 mass% or more. The water content may be less than 100 mass%, 99.900 mass% or less, 99.800 mass% or less, or 99.700 mass% or less. From these viewpoints, the water content may be 90.000 mass% or more and less than 100 mass%.

[0042] The slurry according to the present embodiment may contain a compound having an amide structure and a carboxyl group, or may not contain a compound having an amide structure and a carboxyl group (the content of the compound having an amide structure and a carboxyl group may be substantially 0% by mass based on the total mass of the slurry). Examples of the compound having an amide structure and a carboxyl group include carbamic acid, oxamic acid, malonamic acid, succinamic acid, glutaramic acid, adipamic acid, maleamic acid, fumaramic acid, phthalamic acid, isophthalamic acid, terephthalamic acid, asparagine, and glutamine. The content of the compound having an amide structure and a carboxyl group may be less than 0.01% by mass based on the total mass of the slurry.

[0043] The slurry according to the present embodiment may contain a chelating agent or may not contain a chelating agent (the content of the chelating agent may be substantially 0% by mass based on the total mass of the slurry). Examples of the chelating agent include ethylenediaminetetraacetic acid, ethylenediaminetetra(methylenephosphonic acid), N-(2-hydroxyethyl)ethylenediaminetriacetic acid, 1,3-propanediaminetetraacetic acid, diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, 2-hydroxypropane-1,3-diaminetetraacetic acid, glycoletherdiamine-N,N,N',N'-tetraacetic acid, (S,S)-ethylenediaminedisuccinic acid, L-aspartic acid-N,N-diacetic acid, and dicarboxymethylglutamic acid. The content of the chelating agent may be less than 0.02% by mass or less than 0.01% by mass based on the total mass of the slurry.

[0044] The slurry according to the present embodiment may contain an alkylamine, or may not contain an alkylamine (the content of the alkylamine may be substantially 0% by mass based on the total mass of the slurry). The content of the alkylamine may be less than 0.001% by mass based on the total mass of the slurry.

[0045] The slurry according to the present embodiment may contain a monocarboxylic acid or may not contain a monocarboxylic acid (the content of the monocarboxylic acid may be substantially 0% by weight based on the total weight of the slurry). The content of the monocarboxylic acid may be less than 0.003% by weight or less than 0.001% by weight based on the total weight of the slurry.

[0046] The slurry according to the present embodiment may contain a nonionic polymer, or may not contain a nonionic polymer (the content of the nonionic polymer may be substantially 0% by mass based on the total mass of the slurry). Examples of the nonionic polymer include polyglycerin. The content of the nonionic polymer may be less than 0.0002% by mass or less than 0.0001% by mass based on the total mass of the slurry.

[0047] The slurry according to the present embodiment may contain iodine or may not contain iodine (the iodine content may be substantially 0% by mass based on the total mass of the slurry). The iodine content may be less than 0.1% by mass based on the total mass of the slurry.

[0048] The slurry according to the present embodiment may contain protein or may not contain protein (the protein content may be substantially 0% by mass based on the total mass of the slurry). The protein content may be less than 0.0001% by mass based on the total mass of the slurry.

[0049] The slurry according to the present embodiment may contain polyamide or may not contain polyamide (the polyamide content may be substantially 0% by mass based on the total mass of the slurry). The polyamide content may be less than 0.0001% by mass based on the total mass of the slurry.

[0050] The slurry according to the present embodiment may contain oligosaccharides or may not contain oligosaccharides (the content of oligosaccharides may be substantially 0% by mass based on the total mass of the slurry). The content of oligosaccharides may be less than 0.1% by mass based on the total mass of the slurry.

[0051] The slurry according to the present embodiment may contain starch or may be free of starch (the starch content may be substantially 0% by weight based on the total weight of the slurry), and the starch content may be less than 0.01% by weight or less than 0.001% by weight based on the total weight of the slurry.

[0052] The slurry according to this embodiment may not contain cyclodextrin (the cyclodextrin content may be substantially 0% by weight based on the total weight of the slurry), and the cyclodextrin content may be less than 0.01% by weight or less than 0.001% by weight based on the total weight of the slurry.

[0053] The slurry according to this embodiment may not contain a hydroxy acid (e.g., a hydroxy acid having one carboxy group and one to three hydroxy groups) (the content of the hydroxy acid may be substantially 0% by mass based on the total mass of the slurry). The content of the hydroxy acid (e.g., a hydroxy acid having one carboxy group and one to three hydroxy groups) may be less than 0.01% by mass based on the total mass of the slurry.

[0054] The slurry according to the present embodiment may not contain a polyol, and may not contain a polyether polyol (the polyol content or the polyether polyol content may be substantially 0% by mass based on the total mass of the slurry). The polyol content or the polyether polyol content may be 0.1% by mass or less, less than 0.05% by mass, or 0.01% by mass or less based on the total mass of the slurry.

[0055] The slurry according to the present embodiment may contain a cationic compound or may not contain a cationic compound (the content of the cationic compound may be substantially 0% by mass based on the total mass of the slurry). The cationic compound is a compound having a cationic group in the molecule. Examples of the cationic group include an amino group (a functional group obtained by removing a hydrogen atom from ammonia, a primary amine, or a secondary amine), an ammonium group (a primary, secondary, tertiary, or quaternary ammonium group), an imino group, and a cyano group. Examples of the cationic compound include lauryl trimethyl ammonium chloride, trimethyl-2-methacryloyloxyethyl ammonium chloride, and 3-(methacryloylamino)propyl trimethyl ammonium chloride. The cationic compound may be a cationic compound having a weight average molecular weight of less than 1000, and the slurry according to the present embodiment may not contain a cationic compound having a weight average molecular weight of less than 1000. The content of the cationic compound may be less than 0.0001% by mass based on the total mass of the slurry.

[0056] The slurry according to this embodiment may not contain at least one selected from the group consisting of hydroxy acids, polyols (excluding compounds corresponding to hydroxy acids), and cationic compounds having a weight average molecular weight of less than 1000 (excluding compounds corresponding to hydroxy acids or polyols) (the content of at least one selected from the group consisting of hydroxy acids, polyols, and cationic compounds having a weight average molecular weight of less than 1000 may be substantially 0% by mass based on the total mass of the slurry).

[0057] The slurry according to the present embodiment may not contain a compound having a weight average molecular weight of 1000 or more, and may not contain a compound having a weight average molecular weight of 3000 or more (the content of the compound having a weight average molecular weight of 1000 or more, or the content of the compound having a weight average molecular weight of 3000 or more may be substantially 0 mass% based on the total mass of the slurry). The content of the compound having a weight average molecular weight of 1000 or more, or the content of the compound having a weight average molecular weight of 3000 or more may be 0.1 mass% or less, less than 0.1 mass%, 0.01 mass% or less, less than 0.01 mass%, or 0.001 mass% or less based on the total mass of the slurry.

[0058] The slurry according to the present embodiment may not contain a compound having at least one selected from the group consisting of a hydroxy group and an amide group (e.g., a compound having a weight average molecular weight of 3000 or more) (the content of the compound may be substantially 0 mass% based on the total mass of the slurry). The content of the compound having at least one selected from the group consisting of a hydroxy group and an amide group (e.g., a compound having a weight average molecular weight of 3000 or more) may be 0.1 mass% or less, less than 0.1 mass%, 0.01 mass% or less, less than 0.01 mass%, or 0.001 mass% or less based on the total mass of the slurry. The slurry according to the present embodiment may be an embodiment in which the compound does not contain a compound having at least one selected from the group consisting of a hydroxy group and an amide group (e.g., a compound having a weight average molecular weight of 3000 or more) and the content of the compound X is within each of the above-mentioned ranges based on the total mass of the slurry (e.g., 0.30 mass% or less).

[0059] The pH of the slurry according to the present embodiment may be in the following ranges from the viewpoint of adjusting the polishing rate of silicon oxide. The pH of the slurry may be 1.0 or more, 2.0 or more, more than 2.0, more than 2.7, 2.8 or more, 3.0 or more, more than 3.0, 3.3 or more, 3.4 or more, 3.5 or more, 3.7 or more, 4.0 or more, more than 4.0, 4.5 or more, 4.6 or more, 4.8 or more, 5.0 or more, more than 5.0, 5.5 or more, or 5.6 or more. The pH of the slurry may be 12 or less, 10 or less, 8.0 or less, 7.0 or less, less than 7.0, 6.5 or less, 6.0 or less, less than 6.0, 5.6 or less, 5.5 or less, 5.0 or less, less than 5.0, 4.8 or less, 4.6 or less, 4.5 or less, 4.0 or less, less than 4.0, 3.7 or less, 3.5 or less, or 3.4 or less. From these viewpoints, the pH of the slurry may be from 1.0 to 12, from 2.0 to 7.0, or from 3.0 to 6.0.

[0060] The pH of the slurry according to this embodiment can be measured with a pH meter (e.g., model number PHL-40 manufactured by DKK-TOA Corporation). For example, after two-point calibration of the pH meter using a phthalate pH buffer solution (pH: 4.01) and a neutral phosphate pH buffer solution (pH: 6.86) as standard buffer solutions, the electrodes of the pH meter are placed in the slurry and the pH value is measured after stabilization for at least two minutes. At this time, the liquid temperatures of both the standard buffer solution and the slurry are 25°C.

[0061] As a parameter given in a dispersion (abrasive dispersion) obtained by adjusting the content of abrasive grains in the slurry according to this embodiment to 5.0 mass %, a parameter Y (Rsp / S, unit: g / m) calculated by the following formula is used. 2), the polishing rate ratio of silicon oxide to silicon nitride (polishing rate of silicon oxide / polishing rate of silicon nitride) can be adjusted. When the polishing rate ratio of silicon oxide to silicon nitride is improved, it is suitable for the application of selectively polishing (removing) silicon oxide to silicon nitride. Parameter Y is a value at 25°C. The content of abrasive grains in the slurry according to this embodiment can be adjusted by diluting or concentrating the slurry. For example, dispersion A containing 5.0% by mass of abrasive grains is diluted twice (mixed with an amount of pure water equivalent to that of dispersion A) and then heated (for example, heated at 40°C for 14 hours), and further mixed with pure water to adjust the content of abrasive grains to 5.0% by mass. Dispersion A and dispersion B can give the same parameter Y. The ratio of the content of other additives (components other than abrasive grains and water, for example, compound X) to the content of abrasive grains in the dispersion is the same as that of the slurry. When the content of the abrasive grains in the slurry according to the present embodiment is 5.0 mass %, the slurry can be used as a dispersion liquid. The content of the abrasive grains can be confirmed, for example, by ICP atomic emission spectrometry. Y = Rsp / total surface area of ​​abrasive grains S = {(reciprocal of NMR relaxation time of dispersion) / (reciprocal of NMR relaxation time when abrasive grains are removed from dispersion)-1} / total surface area of ​​abrasive grains S

[0062] Rsp is an index of the affinity (hydrophilicity) of the abrasive surface to the solvent (water molecules). By dividing Rsp by the total surface area S of the abrasive, the hydrophilicity of the abrasive surface can be evaluated while eliminating the effects of the total surface area of ​​the abrasive. Rsp tends to increase, for example, as the ratio of the content of additives (components other than abrasive and water, such as compound X) to the content of abrasive increases. From the viewpoint of ensuring sufficient measurement accuracy, it is recommended that Rsp be measured when the particle content is sufficient (for example, 1.2 mass% or more).

[0063] The NMR relaxation time can be obtained by pulsed NMR measurement and has a unit of ms. Pulsed NMR measurement is performed by measuring the relaxation time of hydrogen nuclei ( 1This is a method for measuring the transverse relaxation time of H nuclei, and can be performed using a pulsed NMR particle interface characterization device (product name: Acron Area) manufactured by Nippon Rufuto Co., Ltd. The relaxation time can be obtained by the Carr Purcell Meiboom Gill method (CPMG method). The measurement temperature is 25°C.

[0064] The "NMR relaxation time when the abrasive grains are removed from the dispersion liquid" can be measured by preparing a liquid having a composition other than the dispersion liquid except for the abrasive grains. The abrasive grains can also be removed by centrifuging the dispersion liquid at a centrifugal acceleration of 4700G for 30 minutes, and the supernatant obtained by this centrifugation can also be used to measure the "NMR relaxation time when the abrasive grains are removed from the dispersion liquid." The unit of the total surface area S of the abrasive grains is m 2 / g, and the BET surface area can be used as the total surface area S of the abrasive grains.

[0065] In a dispersion liquid obtained by adjusting the content of abrasive grains in the slurry according to this embodiment to 5.0 mass %, the parameter Y calculated by the above formula is set to 0.120 g / m from the viewpoint of easily improving the polishing rate ratio of silicon oxide to silicon nitride. 2 More than 0.125g / m 2 More than 0.130g / m 2 More than 0.135g / m 2 More than 0.140g / m 2 or more than 0.145 g / m 2 That may be the case. The reason why the polishing rate ratio of silicon oxide to silicon nitride is improved is not necessarily clear, but the present inventors speculate that it is as follows. That is, silicon nitride is more hydrophobic than silicon oxide (e.g., silicon oxide derived from TEOS). In this case, in a slurry that gives a dispersion liquid with a large parameter Y and high hydrophilicity, the abrasive grains act less on silicon nitride than silicon oxide, and more easily on silicon oxide than silicon nitride, so that the polishing rate ratio of silicon oxide to silicon nitride is improved. However, the reason is not limited to the above.

[0066] The parameter Y is set to 0.200 g / m from the viewpoint of improving the polishing rate ratio of silicon oxide to silicon nitride. 2 Below, 0.190g / m 2 Below, 0.180g / m 2 Below, 0.170g / m 2 Below, 0.160g / m 2 Below, 0.155g / m 2 Less than or equal to 0.150 g / m 2 From these viewpoints, the parameter Y may be 0.120 to 0.200 g / m 2 The parameter Y may be 0.150 g / m 2 More than 0.155g / m 2 More than 0.160g / m 2 More than 0.170g / m 2 or more than 0.180g / m 2 It may be more than that.

[0067] In the polishing method according to the present embodiment, the surface to be polished is polished using the slurry according to the present embodiment. According to the polishing method according to the present embodiment, the polishing rate of silicon oxide can be improved. The surface to be polished may contain silicon oxide, and may contain silicon oxide derived from TEOS. The material to be polished having the surface to be polished may be a single material or a plurality of materials. The material to be polished may be in the form of a film (polished film), may be a silicon oxide film, or may be a TEOS film.

[0068] The manufacturing method of the part according to the present embodiment includes a singulation step of singulating a member (a member to be polished; a substrate) having a polished surface polished by the polishing method according to the present embodiment. The singulation step may be, for example, a step of dicing a wafer (e.g., a semiconductor wafer) having a polished surface polished by the polishing method according to the present embodiment to obtain a chip (e.g., a semiconductor chip). As one aspect of the manufacturing method of the part according to the present embodiment, the manufacturing method of the semiconductor part according to the present embodiment includes a step of singulating a member (a member to be polished) having a polished surface polished by the polishing method according to the present embodiment to obtain a semiconductor part (e.g., a semiconductor chip). The manufacturing method of the part according to the present embodiment may include a polishing step of polishing the polished surface of the member to be polished by the polishing method according to the present embodiment before the singulation step. The part according to the present embodiment is a part obtained by the manufacturing method of the part according to the present embodiment, and may be a semiconductor part, a chip (e.g., a semiconductor chip), or the like.

[0069] The manufacturing method of the bonded body according to the present embodiment includes a bonding step of bonding the bonding surface of the polished member polished by the polishing method according to the present embodiment, or the bonding surface of the part obtained by the manufacturing method of the part according to the present embodiment (for example, the bonding surface of the semiconductor part obtained by the manufacturing method of the semiconductor part according to the present embodiment) to the bonding surface of the bonded body. The bonding surface of the polished member or the bonding surface of the part may be the polished surface polished by the polishing method according to the present embodiment. The bonded body to be bonded to the polished member or part may be the polished member polished by the polishing method according to the present embodiment, or the part obtained by the manufacturing method of the part according to the present embodiment, and may be a bonded body different from these polished members and parts. In the bonding step, when the bonding surface of the polished member or part has a metal part and the bonding surface of the bonded body has a metal part, the metal parts may be brought into contact with each other. The metal part may contain copper. The bonded body according to the present embodiment is a bonded body obtained by the manufacturing method of the bonded body according to the present embodiment.

[0070] The electronic device according to the present embodiment includes at least one member selected from the group consisting of a member (polished member) having a polished surface polished by the polishing method according to the present embodiment, the component according to the present embodiment, and the bonded body according to the present embodiment. EXAMPLES

[0071] The present disclosure will be specifically described below based on examples, but the present disclosure is not limited thereto.

[0072] <Slurry preparation> (Examples 1 to 7 and Comparative Examples 1 to 8) The additives shown in Table 1 were added to a liquid containing colloidal ceria particles (manufactured by Solvay, product name: Zenus (registered trademark) HC60, particle content: 30 mass%). Water was then added and the particle size was adjusted to obtain slurry A containing 5.0 mass% colloidal ceria particles (abrasive grains) and additives. The additive content in slurry A was 2.0 mass% in Example 1 and 0.50 mass% in Examples 2 to 7 and Comparative Examples 1 to 8.

[0073] As the additives, the following compounds were used. Examples 1 and 2: Trimethylolethane (dH=24.0, dD=17.9, dP=10.1) Example 3: 2,2-bis(hydroxymethyl)propionic acid (dH=23.6, dD=17.7, dP=10.2) Example 4: α-Thioglycerol (dH=22.0, dD=18.6, dP=11.1) Example 5: 2,2-bis(hydroxymethyl)butyric acid (dH=21.4, dD=17.3, dP=9.4) Example 6: 2-Hydroxyisobutyric acid (dH=19.4, dD=16.9, dP=9.2) Example 7: Allantoin (dH=19.1, dD=20.8, dP=24.4) Comparative Example 1: 4-Aminobenzoic acid (dH=14.6) Comparative Example 2: 3-Hydroxypyridine (dH=13.7) Comparative Example 3: 4-Hydroxypyridine (dH = 13.7) Comparative Example 4: Acetic acid (dH = 13.6) Comparative Example 5: Nicotinamide (dH = 12.8) Comparative Example 6: 2-Pyridineethanol (dH = 12.7) Comparative Example 7: Acetanilide (dH = 8.5) Comparative Example 8: 2-Acetylpyridine (dH = 6.3)

[0074] The above hydrogen bonding term dH, dispersion term dD, and polarization term dP of the Hansen solubility parameters for each additive were calculated by the Practical Hansen Solubility Parameters (HSPiP) program (ver. 5.3.02).

[0075] (Comparative Example 9) Water was added to a liquid containing colloidal ceria particles (manufactured by Solvay, trade name: Zenus (registered trademark) HC60, particle content: 30% by mass), and then the particle size was adjusted to obtain slurry A containing 5.0% by mass of colloidal ceria particles (abrasive grains).

[0076] <Preparation of polishing liquid> By adding water to the above slurry A, slurry B (polishing liquid) containing 0.25% by mass of colloidal ceria particles (abrasive grains) was prepared. The slurry B of Examples 1 to 7 and Comparative Examples 1 to 8 further contained the additives shown in Table 1, and the content of the additives was 0.10% by mass in Example 1 and 0.025% by mass in Examples 2 to 7 and Comparative Examples 1 to 8 based on the total mass of slurry B.

[0077] <Measurement of pH> The pH of slurry B was measured using a pH meter (model number: PHL-40 manufactured by Toa DKK Corporation). The pH meter was calibrated at two points using a phthalate pH buffer solution (pH: 4.01) and a neutral phosphate pH buffer solution (pH: 6.86) as standard buffer solutions. After that, the electrode of the pH meter was placed in slurry B, and the value after more than 2 minutes had passed and it had stabilized was measured. The measurement results are shown in Table 1.

[0078] <Measurement of average particle size> The average particle size D50 and volume average particle size MV of the colloidal ceria particles in slurry B were measured using a Microtrac MT3300EXII manufactured by Microtrac Bell Co., Ltd. The measurement results are shown in Table 1.

[0079] <Measurement of parameter Y> The slurry A (abrasive grain content: 5.0% by mass) of the embodiment was centrifuged at a centrifugal acceleration of 4700G for 30 minutes to settle the abrasive grains, and the supernatant was removed. Next, the abrasive grains were obtained by vacuum drying at room temperature (25°C) for 24 hours, and then the abrasive grains were vacuum dried at 100°C for 1 hour. Then, a BET specific surface area measuring device (manufactured by Anton Paar, product name: autosorb iQ) was used to perform measurement by a gas adsorption method using nitrogen gas as an adsorption medium. The total surface area S of the abrasive grains was obtained by analysis using the multi-point BET method.

[0080] Next, slurry A (abrasive grain content: 5.0 mass%) was prepared as measurement sample A. Also, measurement sample B was prepared by adding water to the additives in Table 1. The additive content in measurement sample B was 2.0 mass% in Example 1, and 0.50 mass% in Examples 2 to 7. Measurement sample B had a composition in which the abrasive grains were removed from measurement sample A. Next, the NMR relaxation time (25°C) was measured for these measurement samples A and B using a pulse NMR type particle interface characteristic evaluation device (manufactured by Nippon Luft Co., Ltd., product name: Acron Area). Then, Rsp was calculated based on the following formula, and then Rsp was divided by the total surface area S of the abrasive grains to obtain a parameter Y (Rsp / S). The results are shown in Table 1. Y = Rsp / total surface area of ​​abrasive grains S = {(reciprocal of NMR relaxation time of measurement sample A) / (reciprocal of NMR relaxation time of measurement sample B)-1} / total surface area of ​​abrasive grains S

[0081] <Polishing evaluation> In a polishing apparatus (manufactured by APPLIED MATERIALS, product name: Mirra3400), a substrate having a film to be polished (silicon oxide film (TEOS film) or silicon nitride film (SiN film)) formed on a φ200 mm silicon wafer was set on a holder for mounting the substrate to which an adsorption pad was attached. The holder was placed on a platen to which a porous urethane resin pad was attached, so that the film to be polished faced the pad. While each of the above-mentioned slurries B was supplied onto the pad at a supply rate of 200 mL / min, the substrate was pressed against the pad with a polishing load of 20 kPa. At this time, the platen was kept in a constant state for 78 min. -1 , Holder 98min -1 Polishing was performed by rotating at 400°C for 1 minute. After polishing, the substrate was thoroughly washed with pure water and then dried. An optical interference type film thickness measuring device was used to measure the change in film thickness before and after polishing to determine the polishing speed (TEOS RR and SiN RR, unit: Å / min). In addition, the polishing speed ratio of silicon oxide to silicon nitride (TEOS RR / SiN RR) was calculated. The results are shown in Table 1.

[0082] [Table 1]

Claims

1. Contains abrasive grains, compound X, and water; the abrasive grains include cerium oxide; The hydrogen bond term dH of the Hansen solubility parameter of the compound X is 15.0 MPa. 1/2 or more (however, excluding a polishing liquid containing abrasive grains, a hydroxy acid, a polymer compound having at least one selected from the group consisting of a hydroxyl group and an amide group, and a liquid medium, wherein the abrasive grains have a positive zeta potential, and the polymer compound has a weight average molecular weight of 3,000 or more).

2. A slurry containing an abrasive grain, a compound X, and water, the abrasive grains include cerium oxide; The compound X has a hydrogen bond term dH of Hansen solubility parameter of 15.0 MPa 1 / 2 or more; A slurry, in which a content of the abrasive grains in the slurry is adjusted to 5.0 mass %, and in a dispersion obtained by adjusting the content of the abrasive grains in the slurry to 5.0 mass %, a parameter Y calculated by the following formula is 0.120 g / m 2 or more. Y = {(reciprocal of the NMR relaxation time of the dispersion) / (reciprocal of the NMR relaxation time when the abrasive grains are removed from the dispersion)-1} / total surface area S of the abrasive grains

3. 3. The slurry of claim 1 or 2, wherein the abrasive is colloidal.

4. 4. The slurry according to claim 1, wherein the content of the cerium oxide is 99 mass % or more based on the total amount of the abrasive grains contained in the slurry.

5. The slurry of any one of claims 1 to 4, wherein compound X comprises hydroxyisobutyric acid.

6. The slurry of any one of claims 1 to 5, wherein compound X comprises 2,2-bis(hydroxymethyl)butyric acid.

7. The slurry of any one of claims 1 to 6, wherein compound X comprises 2,2-bis(hydroxymethyl)propionic acid.

8. The slurry according to any one of claims 1 to 7, wherein the content of the compound X is 0.50% by mass or less, based on the total mass of the slurry.

9. The slurry of any one of claims 1 to 8, having a pH of from 3.0 to 6.

0.

10. A polishing method comprising polishing a surface to be polished with the slurry according to any one of claims 1 to 9.

11. The polishing method according to claim 10 , wherein the surface to be polished comprises silicon oxide.

12. A method for producing a semiconductor component, comprising the steps of: obtaining a semiconductor component by dicing a member having a surface to be polished that has been polished by the polishing method according to claim 10 or 11 into individual pieces.

Citation Information

Patent Citations

  • Polishing method

    JP1996022970A

  • Cerium oxide abrasive agent and polishing method of substrate

    JP1998106994A

  • CMP polishing liquid, and polishing method

    WO2016006553A1

  • Polishing liquid, polishing liquid set, and polishing method

    WO2019182061A1